2014
DOI: 10.1177/0194599814557468
|View full text |Cite
|
Sign up to set email alerts
|

Voice Assessment and Voice‐related Quality of Life in Patients with Benign Thyroid Disease

Abstract: Patients with benign thyroid diseases had lower scores in vocal self-assessment, the clinical evaluation of voice, and the V-RQOL. These dimensions of voice assessment showed correlations ranging from mild to moderate and should complement the clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…This result corroborates the conclusion of studies with thyroid benign disease patients 5 , and suspicion of thyroid cancer 23 . Probably the results are original from the physical discomfort related to the symptoms and the voice features of this population [10][11][12] , which are perceptible regardless the subjects' voice demand and profession, and lately the subject perceives the interference in social and daily activities, and the amount these limitations impact emotionally.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This result corroborates the conclusion of studies with thyroid benign disease patients 5 , and suspicion of thyroid cancer 23 . Probably the results are original from the physical discomfort related to the symptoms and the voice features of this population [10][11][12] , which are perceptible regardless the subjects' voice demand and profession, and lately the subject perceives the interference in social and daily activities, and the amount these limitations impact emotionally.…”
Section: Resultssupporting
confidence: 90%
“…The index are similar to a study analyzing the voice-related quality of life of 67 women with benign thyroid disease diagnose, and mean age of 44.7±14.8 years, as follow: 76.25, 77.72, and 73.09 to the physical, socio-emotional domain, and total, respectively. The study also concluded the patients with benign thyroid disease have high frequency of voice complaints and their voices have negative impact on quality of life 5 . Yet in studies analyzing patients with suspicion of thyroid cancer the index found were slight higher of 84.21, 92.86, and 85.00 to physical, socioemotional, and total domain respectively 23 .…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations